On a scarab from Colle del Forno: some considerations on the globular style production (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
The scarab from Colle del Forno necropolis presented in this note gives the opportunity for some very brief considerations regarding to the globolo-style production, considering also the recent synthesis work by Ulf Hannson, that is at now a very useful update regarding to stylistic, formal, iconographical questions, to the production aspects and represents as well a good integration of the corpus already build up by Peter Zazoff.
Keywords: scarab; style; a globolo; globular; Etruscan glyptic; Hannson; Zazoff; Colle del Forno